Streptococcus pyogenes Meningitis in a Pediatric Patient: Case Report - Torres, Lara (2023)
Streptococcus pyogenes causes a wide spectrum of diseases in children. However, meningitis due to this pathogen is highly uncommon. Although rare, it is associated with a high case fatality rate and can result in severe neurological sequelae. We report a case of Streptococcus pyogenes meningitis in a previously healthy 3-year-old boy. The purpose of this case report is to emphasize that this agent should be considered a cause of meningitis in previously healthy infants because of its frequent association with complications, sequelae, and high mortality rates.